1996
DOI: 10.1007/bf02787820
|View full text |Cite
|
Sign up to set email alerts
|

Performance of a magnetically stabilized bed reactor with immobilized yeast cells

Abstract: This paper is focused on the possibility to apply the magnetic stabilization technique in bioprocessing. The feasibility of a continuous ethanol fermentation process with immobilized Saccharomyces cerevisiae cells in a magnetically stabilized bed (MSB) was demonstrated. The fermentation processes were carried out in an external magnetic field, transverse to the fluid flow. The flexibility to change the bed expansion owing to the independent change of the fluid flow and the field intensity (the "magnetization F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0
6

Year Published

2000
2000
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 17 publications
1
34
0
6
Order By: Relevance
“…It was later confirmed that at this magnetic flux intensity, the yeast metabolic rate increased (Motta et al, 2001). Continuous fermentations using 80 to 260 mT SMF intensity flow transversal to the drainage flux resulted gain of 75% in the alcohol production with a 27% glucose consumption growth, compared to the conventional bed percentages (Ivanova et al, 1995). The yeast ethanolic fermentation is known to be directly related to the carbonic gas production (Tadege, et al 1999) so, higher is CO 2 production, greater is the biomass.…”
Section: Introductionmentioning
confidence: 79%
“…It was later confirmed that at this magnetic flux intensity, the yeast metabolic rate increased (Motta et al, 2001). Continuous fermentations using 80 to 260 mT SMF intensity flow transversal to the drainage flux resulted gain of 75% in the alcohol production with a 27% glucose consumption growth, compared to the conventional bed percentages (Ivanova et al, 1995). The yeast ethanolic fermentation is known to be directly related to the carbonic gas production (Tadege, et al 1999) so, higher is CO 2 production, greater is the biomass.…”
Section: Introductionmentioning
confidence: 79%
“…In a watery medium, they arrange themselves spontaneously to form double-layered membranes with a central core made from their water hating ends. Their water loving phosphate ends face outwards towards the water [12].…”
Section: Detection the Effect Of Magnetic Field Energy On The Growth mentioning
confidence: 99%
“…However, not all positive ions stabilize the membrane equally well. Calcium ions are particularly good because of their double positive charge, but monovalent potassium, with just one charge, is only ordinary [10][11][12][13].…”
Section: Detection the Effect Of Magnetic Field Energy On The Growth mentioning
confidence: 99%
“…Dessa forma, as principais diferenças em relação aos trabalhos encontrados em literatura foram (IVANOVA et al, 1996;MOTTA et al 2001;MOTTA et al, 2004;PEREZ et al, 2007): (i) avaliar a influência de campos magnéticos de 250-420-5000 Gauss, ou seja, com um intervalo amplo; (ii) avaliar a influência de campos magnéticos divergentes; (iii) avaliar a influência de campos magnéticos gerados por condicionador e imãs; (iv) avaliar a influência de diferentes tipos de biorreatores -tubo de ensaio e fermentadores; (v) utilizar Saccharomyces cerevisiae comercial em intervalo de concentração celular desde valor reduzido até próximo ao valor utilizado industrialmente (0,2 a 30 g.L -1 ); e (vi) utilizar concentração de substrato desde valor reduzido até próximo ao valor utilizado industrialmente (20 a 170 g.L -1 ).…”
Section: Influência De Campo Magnético Na Fermentação Alcoólica Descounclassified
“…Ivanova et al (1996) analisaram a viabilidade da aplicação de campo magnético de 800 a 2600 Gauss no processo de fermentação contínua para a produção de etanol, com células de Saccharomyces cerevisiae imobilizadas e meio de cultura composto por glicose com concentração de 110-180 g.L -1 e nutriente a 32 ºC. O processo de fermentação foi realizado com campo magnético transversal ao escoamento do fluido.…”
Section: Introductionunclassified